PENGARUH LAMA PENYIMPANAN SEMEN AYAM KAMPUNG PADA SUHU 5^oC TERHADAP ABNORMALITAS SPERMATOZOA DAN FERTILITAS TELUR HASIL INSEMINASI BUATAN DENGAN AYAM NIAGA PETELUR - Muhammad Arfan Nur Ardiansyah; Dadang Mulyadi Saleh; Nu'man Hidayat (Fakultas Peternakan Universitas Jenderal Soedirman, 2022)
Background. The purpose of the study was to find out the long-lasting effect of storage on the abnormality and fertility of spermatozoa of domestic chickens. Materials and Methods. The material used is 11 roosters aged 10-12 months, 40 laying commercial chickens are ready for production by feeding as much as 120 gr / head / day for laying commercial chickens and 150gr / tail / day for roosters. The research design used is a Complete Random Design with four treatments namely: P0: fresh semen + (skim milk 75% + egg yolk 25%) + storage 0 hours., P1: fresh semen + (skim milk 75% + egg yolk 25%) + storage 1 hour., P2: fresh semen + (skim milk 75 % + egg yolk 25%) + 2 hours storage., P3: fresh semen + (skim milk 75% + egg yolk 25%) + storage 3 hours. There are 5 repeats in each treatment resulting in a total of 20 experimental units. Results. The results showed that the most ended abnormality was in the treatment of 0 hours storage length (11.5%) and the highest abnormality was in the 3-hour storage length treatment (15.4%) while the highest yield of egg fertility was also present in the treatment of 0 hours storage length (14.6%) and lowest at P2 (1.82%). Conclusion. It can be concluded that research shows the length of storage has an unreal effect (P>0.05) on spermatozoa abnormality and egg fertility.